Corporate environmental, social, and governance activities and financial reporting quality: An international investigation - Özer, Gökhan; Aktas, Nagihan; Çam, İlhan (Elsevier, 2024)
This paper examines the impact of firms' environmental, social, and governance (ESG) activities on financial reporting quality (FRQ). The study uses 45,877 firm-year observations from 65 countries between 2003 and 2021. In the research model, firm characteristics and macroeconomic and institutional structure characteristics of the countries are controlled for. This study finds that firms with higher ESG scores have higher FRQ. Additionally, our mediation analysis indicates that financial distress costs serve as a crucial mechanism through which ESG influences FRQ. Our findings are robust after accounting for alternative measures of FRQ, different sampling scenarios, endogeneity issues, and simultaneity bias.
Keywords: Corporate sustainability; Earnings management; ESG; Financial reporting quality